Rapid Hydrogen Peroxide Release during Coral-Bacteria Interactions - Armoza-Zvuloni, Rachel; Schneider, Avi; Shaked, Yeala (Frontiers in Marine Science, 2016)
Ocean warming has exacerbated the severity of coral diseases, many of which are mediated by pathogenic bacteria. In response to the presence of pathogens various organisms activate an oxidative burst response, involving strong and rapid generation of reactive oxygen species (ROS) that serve both as bactericides and as signals for other defense systems. While many components of the coral immune systems are being unveiled, an oxidative burst response, triggered by bacteria proximity, has not yet been reported. Hydrogen Peroxide (H2O2), one of the ROS produced during the oxidative burst, is often monitored as an indicator of this pathway. Here we report a yet undescribed release of H2O2 from the coral Stylophora pistillata upon contact with bacteria. In a series of short term experiments we monitored H2O2 concentrations in the vicinity of S. pistillata prior to and following local administration of five bacteria isolates belonging to the genus Vibrio (obtained from healthy S. pistillata). In most experiments, rapid H2O2 release was recorded at the site of interaction within one min from Vibrio addition and persisted for the remaining 5 min of the experiment. In some experiments, discrete or continuous drop of H2O2 to below background levels were seen following Vibrio addition. This H2O2 loss was quantitatively accounted for by the bacterial antioxidants and implies that Vibrio may at times offset the coral released H2O2.The total H2O2 released by the coral from the small interaction site ( 10 mm2) was 200–600 pmol, which may build up to a concentration of 20 μM in the coral diffusive boundary layer. H2O2 concentrations above 10 μM resulted in significant mortality of the coral pathogen Vibrio coralliilyticus, suggesting that the released H2O2 may act as a bactericide. It is thus far unclear if this H2O2 release is part of an oxidative burst response, but it's occurrence strongly indicates that corals sense and chemically react toward bacteria.